2003
DOI: 10.3758/bf03194825
|View full text |Cite
|
Sign up to set email alerts
|

Goal-driven modulation of stimulus-driven attentional capture in multiple-cue displays

Abstract: Six location-cuing experiments were conducted to examine the goal-driven control of attentional capture in multiple-cue displays. In most of the experiments, the cue display consisted of the simultaneous presentation of a red direct cue that was highly predictive of the target location (the unique cue) and three gray direct cues (the standard cues) that were not predictive of the location. The results indicated that although target responses were faster at all cued locations relative to uncued locations, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 59 publications
2
11
0
1
Order By: Relevance
“…However, results from recent studies have suggested that sudden-onsets that occur within 100 ms before a subsequent target (and in the same location) can enhance target performance through sensory activation or summation, rather than through exogenous attentional capture (see Richard, Wright, & Ward, 2003; Wright & Richard, 2003). In the case of a single pre-cue that occurs on its own, as in Experiments 1 and 2 of the current study, Wright and colleagues (Wright & Richard, 2003) showed that the total impact of the pre-cue on subsequent target performance is best explained as a combination of sensory activation and exogenous attentional capture.…”
Section: Methodsmentioning
confidence: 99%
“…However, results from recent studies have suggested that sudden-onsets that occur within 100 ms before a subsequent target (and in the same location) can enhance target performance through sensory activation or summation, rather than through exogenous attentional capture (see Richard, Wright, & Ward, 2003; Wright & Richard, 2003). In the case of a single pre-cue that occurs on its own, as in Experiments 1 and 2 of the current study, Wright and colleagues (Wright & Richard, 2003) showed that the total impact of the pre-cue on subsequent target performance is best explained as a combination of sensory activation and exogenous attentional capture.…”
Section: Methodsmentioning
confidence: 99%
“…The sequence of events that characterizes the allocation of spatial attention by a visual signal, spatial visual attention, is well understood. Shortly after attention is captured (Jonides, 1981) by a visual event in the periphery, the processing of additional stimuli is facilitated at that location and hindered elsewhere (Wright & Richard, 2000; Richard et al. , 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Another paradigm, however, has prompted some researchers to suggest that a unitary attentional focal point can be divided into multiple foci. If two or more direct cues are presented simultaneously, cue effects can occur when targets appear at any of the cued locations (e.g., Richard, Wright, & Ward, 2003;Wright, 1994;Wright, Richard, & McDonald, 1996). It could be argued that this occurs because attention has been divided into discrete multiple foci so that it can be directed simultaneously to each cued location (see, e.g., Kramer & Hahn, 1995).…”
mentioning
confidence: 99%